The Influence of Viral Marketing, Store Atmosphere, and Brand Trust on Purchasing Decisions: (Study at Bahagia Kalibeber Coffee Shop) - Alfin Setia Pamungkas; Bahtiar Efendi (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Purpose - The development of coffee shops in Wonosobo has caused competition in the coffee shop business to become increasingly fierce, business actors must of course prepare their business marketing systems properly in order to remain competitive. coffee Happy caliber. Methodology - This research is a quantitative study with a population of 104 people using quantitative data analysis techniques for data collection using questionnaires. Statistical data analysis using multiple regression analysis techniques hypothesis testing using f test and t test. Findings - The results of this study 1. Viral marketing has a significant effect on purchasing decisions at Bahagia Kalibeber coffee shop. 2 store atmosphere has a significant effect on purchasing decisions at Bahagia Kalibeber coffee shops. 3 brand trusts have a significant effect on on purchasing decisions at Bahagia Kalibeber coffee shops.